Investigation on Biomass Briquette as Energy Source from Waste Leaf Cerbera Manghas - Willyanto Anggono; Fandi D. Suprianto; Sutrisno Sutrisno; Andreas W. Kasrun (International Journal of Industrial Research and Applied Engineering, 2016)
Indonesia is a tropical country and has abundant varieties of plants but has not been utilized to the fullest. One of the plants that are often encountered in the community is Cerbera manghas. Cerbera manghas is known as one of the trees that have solid roots; thus, it is widely used for adding greenery both on the roadside and the residential areas of Surabaya. Although beneficial for shade and the reduction of air pollution in urban areas, waste from the leaves of this plant become a serious issue for the cleanliness of the city. Organic solid waste that comes from the falling leaves have the potential to be used as a solid fuel alternative in the form of briquettes when processed appropriately. This study aims to investigate the potential of Cerbera manghas leaves waste to be used as raw material of biomass briquettes with tapioca as a binder, to evaluate the property of the resulted briquettes using ultimate analysis, proximate analysis, and also to find the effect of the composition of tapioca to the heating value of the biomass briquettes. Heating values ​​of five mixtures with various tapioca compositions of 10%, 20%, 30%, 40%, and 50% were evaluated using an oxygen bomb calorimeter. The experimental results showed that the biomass briquettes made of Cerbera manghas leaves waste can be made using tapioca as a binder. The greater the percentage of the mass of tapioca in the briquettes, the lower heating value generated. Biomass briquettes made of Cerbera manghas leaves waste can be made into a source of sustainable energy with the optimal composition of 90% waste leaves and 10% tapioca.